Bilateral Breast Metastases from Vulvar Carcinoma: A Case Report and Literature Review - D. C. Papatheodorou; C. G Liakou; K. Kalogerakos; Johannes Carl Athanasios Dimopoulos; N. Kalinoglou (Hindawi Limited, 2017)
Vulvar carcinoma is a rare disease that accounts for 3-5% of all gynecologic malignancies. Breast represents an unusual site of metastasis and only a few cases are reported. We describe the first case of bilateral metastatic breast carcinoma of vulvar origin, at an 80-year-old female patient. Six months after treatment of her primary disease, she presented with bilateral metastatic squamous cell breast carcinoma. Diagnosis was based on clinical, radiological, and histological facts. Breast although rare is another potential site of metastasis in vulvar cancer and thus mammary gland examination should be considered in the follow-up of these patients. Differential diagnosis between primary and metastatic lesions is of utmost importance for appropriate management.